2017
DOI: 10.1016/j.jid.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Performing Skin Microbiome Research: A Method to the Madness

Abstract: Growing interest in microbial contributions to human health and disease has increasingly led investigators to examine the microbiome in both healthy skin and cutaneous disorders, including acne, psoriasis and atopic dermatitis. The need for common language, effective study design, and validated methods are critical for high-quality, standardized research. Features, unique to skin, pose particular challenges when conducting microbiome research. This review discusses microbiome research standards and highlights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
163
1
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 107 publications
(203 reference statements)
0
163
1
14
Order By: Relevance
“…A standard approach for skin microbiome study design, collection, storage, processing and analysis as proposed by Kong et al . should be followed in future studies 17. However, although the list of limitations and sometimes poor evidence might be assessed as a weak recommendation for the inclusion of cutaneous microbiome in dermatological trials, the recent finding that the gut microbiome partially explains the response/nonresponse to PD‐1 immunotherapy in different cancer patients will foster research into microbiome in general 88, 89.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard approach for skin microbiome study design, collection, storage, processing and analysis as proposed by Kong et al . should be followed in future studies 17. However, although the list of limitations and sometimes poor evidence might be assessed as a weak recommendation for the inclusion of cutaneous microbiome in dermatological trials, the recent finding that the gut microbiome partially explains the response/nonresponse to PD‐1 immunotherapy in different cancer patients will foster research into microbiome in general 88, 89.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have described the role and impact of skin microbiome on disease 17, 18, 19, 20, 21, 22. However, to date, no structured review has been conducted to evaluate the feasibility, suitability and potential use of the skin microbiome as biomarker for early phase clinical drug development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, isogarcinol extracted from Garcinia mangostana L. inhibits inflammatory factors in LPS‐stimulated HaCaT cells and ameliorates IMQ‐induced psoriasis‐like skin lesions in mice . There has also recently been increased scientific interest in microbial contributions to healthy skin and cutaneous disorders . Furthermore, metabolomics has been used to study the local and systemic metabolic changes in psoriasis and has revealed novel insights into its pathogenesis and suggested new biochemical signatures .…”
Section: Discussionmentioning
confidence: 99%
“…[23]. Первые клинические дан-ные о наличии связи между патологией кожи и изменениями микробиоты кишечника получены более 10 лет назад.…”
Section: изменения микробиоты при заболеваниях кожиunclassified